Cost effectiveness of community-based and in-patient therapeutic feeding programs to treat severe acute malnutrition in Ethiopia - Tekeste Asayehegn; Wondafrash Mekitie; Azene Girma; Deribe Kebede (Cost Effectiveness and Resource Allocation, 2012)
Abstract Background This study estimated the cost effectiveness of community-based therapeutic care (CTC) for children with severe acute malnutrition (SAM) in Sidama Zone, Ethiopia compared to facility based therapeutic feeding center (TFC). Methods A cost effectiveness analysis comparing costs and outcomes of two treatment programmes was conducted. The societal perspective, which considers costs to all sectors of the society, was employed. Outcomes and health service costs of CTC and TFC were obtained from Save the Children USA (SC/USA) CTC and TFC programme, government health services and UNICEF(in kind supplies) cost estimates of unit costs. Parental costs were estimated through interviewing 306 caretakers. Cost categories were compared and a single cost effectiveness ratio of costs to treat a child with SAM in each program (regardless of outcome) was computed and compared. Results A total of 328 patient cards/records of children treated in the programs were reviewed; out of which 306 (157 CTC and 149 TFC) were traced back to their households to interview their caretakers. The cure rate in TFC was 95.36% compared to 94.30% in CTC. The death rate in TFC was 0% and in CTC 1.2%. The mean cost per child treated was $284.56 in TFC and $134.88 in CTC. The institutional cost per child treated was $262.62 in TFC and $128.58 in CTC. Out of these institutional costs in TFC 46.6% was personnel cost. In contrast, majority (43.2%) of the institutional costs in CTC went to ready to use therapeutic food (RUTF). The opportunity cost per caretaker in the TFC was $21.01 whereas it was $5.87 in CTC. The result of this study shows that community based CTC was two times more cost effective than TFC. Conclusion CTC was found to be relatively more cost effective than TFC in this setting. This indicates that CTC is a viable approach on just economic grounds in addition to other benefits such improved access, sustainability and appropriateness documented elsewhere. If costs of RUTF can be reduced such as through local production the CTC costs per child can be further reduced as RUTF constitutes the highest cost in these study settings.